Development of Assessment Instruments on Technology for Life Materials Based on Wordwall in Typhoon E-Book for Elementary School Students - Tiara*, Yeti; Lestari, Wahyu; Widiarti, Nuni (Riwayat: Educational Journal of History and Humanities, 2024)
The assessment process carried out in schools mostly still uses paper or paper tests, which require high printing costs and when checking the results of the assessment is quite time-consuming, sometimes there are errors in correcting. sometimes distracted by other activities as a teacher. The purpose of this research and development is to help overcome the above problems by developing an assessment instrument in the form of a word game that is certainly liked by children and facilitates the work of teachers. This development research uses the Thiargarajan method with the 4D method. Data collection from interviews, observations, and questionnaires. The results of product validation by a team of validators using Aiken's V formula are valid. Small-scale trials using student and teacher response questionnaires with very good results. In the large-scale trial, 30 students were sampled using Excel and SPSS with a mean N score of 0.8990. 0.7 and N-Percent 89.89% 76 which means valid and reliable.